Canopy Forum: on the interactions of law & religion (Center for the Study of Law and Religion, 2022)
"Canopy Forum is a digital publication from the Center for the Study of Law and Religion at Emory University that produces expert analysis for scholars, lawyers, clergy, journalists, policy makers, and the broader public. We seek to foster productive public discourse on critical issues at the intersection of law and religion – two of the most powerful and pervasive forces in societies around the world"